Prefrontal Cortical Reactivity and Connectivity Markers Distinguish Youth Depression from Healthy Youth. (17th February 2020) - Dhami, Prabhjot; Atluri, Sravya; Lee, Jonathan C; Knyahnytska, Yuliya; Croarkin, Paul E; Blumberger, Daniel M; Daskalakis, Zafiris J; Farzan, Faranak
Abstract: Up to 50% of youth with depression do not respond to conventional first-line treatments. However, little research has been conducted on the pathophysiology of youth depression, hindering the identification of more effective treatments. Our goal was to identify neurophysiological markers that differentiate youth with depression from healthy youth and could serve as targets of novel treatments. We hypothesized that youth with depression would exhibit network-specific cortical reactivity and connectivity abnormalities compared with healthy youth. Transcranial magnetic stimulation combined with electroencephalography and magnetic resonance imaging was employed in combination with clinical and behavioral assessments to study cortical reactivity and connectivity in bilateral dorsolateral prefrontal cortex (DLPFC), motor cortex, and inferior parietal lobule, sites linked to the frontoparietal network, sensorimotor network, and default mode network, respectively. In youth depression, greater cortical reactivity was observed specific to the left and right DLPFC stimulation only, which correlated with anhedonia scores. Additionally, the connectivity of the right DLPFC was significantly higher in youth depression. Source reconstruction attributed the observed connectivity dysregulation to regions belonging to the default mode network. The neurophysiological signatures identified in this study have high potential to inform the development of more effective and targeted interventions for the youth depression population.